(untitled) (Journal of the College of Basic Education, 2022)
Geography of the second intermediate grade students and their attitudes towards the subject. The research sample consisted of (67) students from the second intermediate grade students from Al-Farabi Intermediate School for Boys, affiliated to the General Directorate of Education, Baghdad, Al-Rusafa / the second, for the academic year (2014-2015).The researcher randomly chose Division (B) to represent the experimental group of (35) students, and Division (A) to represent the control group of (32) students.The students of the two groups were rewarded before the start of the experiment in a number of statistical variables, which are the chronological age calculated in months, and the educational attainment of the parents.